Klövviltsarters förhållningssätt till varandra vid utfodringsplatser - Wennhage, Linnea (2022)
Ungulates are an important part of many ecosystems and fill several important ecological roles. In Sweden, the use of artificial feeding sites is a common measure to support wild ungulate populations when food is scarce. The species vary widely in terms of lifestyle, behavior and foraging choices and their inter-specific relationships at the feeding sites are not yet entirely understood. The aim of this study was to investigate the interactions between six species of wild ungulates at feeding sites in the southern parts of Sweden. This was done through analyses of picture and video- material from 17 feeding sites, studying the species’ visits, interactions and behaviour. Fallow deer, red deer and wild boar were the most frequent users of the feeding sites. More multiple-species visits were observed during the colder periods compared to the warmer ones. Few displacements were observed between the species. Fallow deer had a tolerant relationship with red deer and wild boar whereas red deer and wild boar had few interactions. The study showed that agonistic behaviours between ungulate species at artificial feeding sites in southern Sweden are rare, red deer and wild boar seemingly avoided each other at the feeding sites and the vigilance of fallow deer differed with group size, yet their presence had little effect on other species.